Understanding the challenges and gaps in community engagement interventions for COVID-19 prevention strategies in Rohingya refugees: a qualitative study with frontline workers and community representatives - Halder, Charls Erik; Hasan, Md Abeed; Mohamud, Yussuf Mohamed; Nyawara, Marsela; Okello, James Charles; Mizan, Md Nahid; Sayum, Md Abu; Hossain, Ahmed (Frontiers in Public Health, 2023)
Background Rohingya refugees in Bangladesh are vulnerable to infectious diseases such as COVID-19 due to the crowded living conditions with fragile shelters, and limited water, sanitation and hygiene facilities and practices. While risk communication and community engagement (RCCE) is the cornerstone of outbreak control, there is limited evidence available on the effectiveness of the RCCE strategies in this setting. Objectives The goal of this study is to evaluate the effectiveness of RCCE strategies and to explore the challenges and community recommendations in relation to COVID-19 preventive measures in the context of Rohingya refugee camps in Bangladesh. Materials and methods It was a qualitative study. Methods used were (a) observation of RCCE intervention by 3 clinical supervisors accompanying 25 Community Health Workers (CHWs) and (b) 5 focus group discussions engaging 60 community representatives. Data were analyzed using a thematic analysis approach, separately for observation and focus group discussions. Results The study identified a number of good practices of RCCE, including selecting CHWs from the local community, engaging female CHWs, using local dialect, and collaborating with community/religious leaders. Certain good practices need scaling up, such as utilization of multiple communication methods and interpersonal communication skills. Some areas need improvement, such as CHWs being overburdened with multiple tasks, less effort to active listening, repeated delivery of same messages, inadequate linkage to culture, context, and resources, and less effort to empower the community. Engaging the community, five critical themes were identified in relation to poor COVID-19 preventive practices: culture, religion, and language; local context and resources; community trust and interaction with aid workers; communication methods; and gender and social inclusion. Religious misinterpretation, cultural barriers, physical barriers, lack of resources, breach of trust between the community and aid workers, inconsistent/complex messages, lack of gender and social inclusion, and stigmatization are among some key factors. Some key actions were recommended to improve COVID-19 RCCE strategy. Conclusion We urge the RCCE partners to make use of the findings and recommendations to develop a robust RCCE strategy relevant to local culture and context, responsive to people’s concerns and needs, and inclusive of gender, age and social vulnerabilities.